MicroRNA in Teleost Fish - Bizuayehu, Teshome Tilahun (Oxford University Press, 2014)
MicroRNAs (miRNAs) are transcriptional and posttranscriptional regulators involved in nearly all known biological processes in distant eukaryotic clades. Their discovery and functional characterization have broadened our understanding of biological regulatory mechanisms in animals and plants. They show both evolutionary conserved and unique features across Metazoa. Here, we present the current status of the knowledge about the role of miRNA in development, growth, and physiology of teleost fishes, in comparison to other vertebrates. Infraclass Teleostei is the most abundant group among vertebrate lineage. Fish are an important component of aquatic ecosystems and human life, being the prolific source of animal proteins worldwide and a vertebrate model for biomedical research. We review miRNA biogenesis, regulation, modifications, and mechanisms of action. Specific sections are devoted to the role of miRNA in teleost development, organogenesis, tissue differentiation, growth, regeneration, reproduction, endocrine system, and responses to environmental stimuli. Each section discusses gaps in the current knowledge and pinpoints the future directions of research on miRNA in teleosts.